2014
DOI: 10.3109/13685538.2014.968772
|View full text |Cite
|
Sign up to set email alerts
|

The association of metabolic syndrome and aging with cognition in Asian men

Abstract: Not all the metabolic factors were significantly associated with short-term memory or the perceptual capacity domains. Those that were did not show a sufficiently consistent pattern of association to support a role for MetS as a whole in cognitive decline with aging. It may not be meaningful to evaluate the association of MetS as a whole with cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…Increased TG levels after the intake of fat or refined sugars have been associated with impaired spatial memory in young male rats (42) and minipigs (43). These animal studies support findings in elderly people showing negative associations between TG levels and cognitive abilities (44,45). It is thus possible that the memory improvements found in our study were mediated by reduced blood TG levels during testing.…”
Section: Discussionsupporting
confidence: 91%
“…Increased TG levels after the intake of fat or refined sugars have been associated with impaired spatial memory in young male rats (42) and minipigs (43). These animal studies support findings in elderly people showing negative associations between TG levels and cognitive abilities (44,45). It is thus possible that the memory improvements found in our study were mediated by reduced blood TG levels during testing.…”
Section: Discussionsupporting
confidence: 91%
“…Overman et al (2017) found no evidence of a relationship between MetS and memory impairment. Harrison et al (2015) did not find a significant relationship between MetS and memory, these findings being consistent with those of Goh and Hart (2014), Lai et al (2014), and Levin et al (2014). Despite finding a relationship between high blood pressure and other cognitive domains, particularly concerning memory, they did not find significant data.…”
Section: Cognitive Domain: Memorysupporting
confidence: 59%
“… 33 Goh and Hart found high TG levels were positively associated with short-term memory in Asian men. 34 One study showed that triglycerides levels were associated with a decreased risk of Alzheimer’s disease in women. 35 Another study found that high TG levels were negatively correlated with cognitive function in female patients with major depressive disorders.…”
Section: Discussionmentioning
confidence: 99%